A NARRATIVE REVIEW ON THE ROLE OF OXIDATIVE STRESS IN GESTATIONAL DIABETES MELLITUS AND PREECLAMPSIA. - Singh, Ranbir Kumar; Singh, Shreayshi (Student’s Journal of Health Research Africa, 2023)
This review examined the role of oxidative stress in hypertensive disorders of pregnancy (HDP) and metabolic illnesses, including gestational diabetes mellitus. Oxidative stress induces hypoxia in the placenta in preeclampsia (PE) and gestational hypertension (GH). This hypoxia usually causes a systemic inflammatory reaction in the mother. In physical education, the disease causes kidney inflammation and proteinuria. Proteinuria is characterized by urine 8-oxoGuo excretion in preeclampsia. Due to increased insulin synthesis during pregnancy, oxidative stress is linked to gestational diabetes mellitus (GDM). Unregulated insulin release generates lipid peroxidation agents, which inhibit antioxidant secretion. Therefore, reactive oxygen species (ROS) grow dramatically in the cellular environment, inhibiting glucose delivery to diverse organs.